Effect of horseshoe crab perivitelline fluid on the viability of stem cells from human exfoliated deciduous teeth and expression of cell cycle regulatory genes - Ibrahim, Najian; Thirumulu Ponnuraj, Kannan; Ahmad, Azlina; Mokhtar@Makhtar, Khairani Idah (National Institute of Science Communication and Information Resources, 2021)
The effect of perivitelline fluid (PVF) (0.019 mg/ml) on the stem cell viability extracted from human exfoliated deciduous teeth was assessed using LIVE/DEAD viability/cytotoxicity. It showed that PVF enhanced viability as observed by higher live cell percentage and a greater number of viable cells in the treated group for 3 days. The expression of selected cell cycle regulatory genes investigated using reverse transcriptase polymerase chain reaction (RT-PCR) for 21 days showed that CDKN2A, PTEN and TP53 expressed significantly higher in the treated group, suggesting that PVF enhanced SHED growth and proliferation. MDM2 expression remained at low levels in the treated group indicating that PVF did not result in tumorigenic growth. Low expression of apoptotic activator gene, BCL2L11 in treated group from day 1 until 14 with a sudden peak on day 21 was noted. This is deemed normal as the cells thrive to maintain homeostatic level at the 21st day of incubation.